Nuclear Factor Erythroid 2-Related Factor 2 in Regulating Cancer Metabolism - Smolková, Katarína; Mikó, Edit; Kovács, Tünde; Leguina-Ruzzi, Alberto; Sipos, Adrienn; Bai, Péter (Antioxidants & redox signaling, 2020)
Significance: Nuclear factor erythroid 2 (NFE2)-related factor 2 (NFE2L2, or NRF2) is a transcription factor predominantly affecting the expression of antioxidant genes. NRF2 plays a significant role in the control of redox balance, which is crucial in cancer cells. NRF2 activation regulates numerous cancer hallmarks, including metabolism, cancer stem cell characteristics, tumor aggressiveness, invasion, and metastasis formation. We review the molecular characteristics of the NRF2 pathway and discuss its interactions with the cancer hallmarks previously listed. Recent Advances: The noncanonical activation of NRF2 was recently discovered, and members of this pathway are involved in carcinogenesis. Further, cancer-related changes (e.g., metabolic flexibility) that support cancer progression were found to be redox- and NRF2 dependent. Critical Issues: NRF2 undergoes Janus-faced behavior in cancers. The pro- or antineoplastic effects of NRF2 are context dependent and essentially based on the specific molecular characteristics of the cancer in question. Therefore, systematic investigation of NRF2 signaling is necessary to clarify its role in cancer etiology. The biggest challenge in the NRF2 field is to determine which cancers can be targeted for better clinical outcomes. Further, large-scale genomic and transcriptomic studies are missing to correlate the clinical outcome with the activity of the NRF2 system. Future Directions: To exploit NRF2 in a clinical setting in the future, the druggable members of the NRF2 pathway should be identified. In addition, it will be important to study how the modulation of the NRF2 system interferes with cytostatic drugs and their combinations.
Keywords: mutace; regulace genové exprese u nádorů; Animals; cancer; Metabolic Networks and Pathways; Antioxidants; NF-E2-Related Factor 2; oxidační stres; breast cancer; Neoplasms; Gene Expression Regulation, Neoplastic; nádory; Oxidative Stress; reactive species; energetický metabolismus; metabolické sítě a dráhy; lidé; Hormones; NRF2; Energy Metabolism; faktor 2 související s NF-E2; signální transdukce; Mutation; Signal Transduction; cancer metabolism; epigeneze genetická; oxidace-redukce; nádorové biomarkery; Oxidation-Reduction; Neoplastic Stem Cells; mikro RNA; antioxidancia; Epigenesis, Genetic; Biomarkers, Tumor; MicroRNAs; hormony; signální dráha UPR; zvířata; Unfolded Protein Response; nádorové kmenové buňky; Humans